Quantitative measurement of 18F-FDG PET/CT uptake reflects the expansion of circulating plasmablasts in IgG4-related disease. (7th July 2017) - Berti, Alvise; Della-Torre, Emanuel; Gallivanone, Francesca; Canevari, Carla; Milani, Raffaella; Lanzillotta, Marco; Campochiaro, Corrado; Ramirez, Giuseppe Alvise; Bozzalla Cassione, Emanuele; Bozzolo, Enrica; Pedica, Federica; Castiglioni, Isabella; et al.
Abstract: Objective: [ 18 F]Fluorodeoxyglucose ( 18 F-FDG) PET/CT is increasingly used to assess organ involvement and response to treatment in IgG4-related disease (IgG4-RD), but clear correlations between 18 F-FDG uptake and disease activity have not been established yet. We aimed to correlate the intensity and distribution of 18 F-FDG uptake with validated clinical, serological and immunological parameters of IgG4-RD activity. Methods: Twenty patients with active IgG4-RD underwent a baseline 18 F-FDG PET/CT. Ten patients repeated 18 F-FDG PET/CT after immunosuppressive treatments. 18 F-FDG tissue uptake was measured using the standardized uptake value corrected for the partial volume effect (PVC-SUV) and the total lesion glycolysis (TLG) with (TLGtot+ln ) and without (TLGtot−ln ) lymph nodes. Disease activity was assessed by means of clinical parameters [IgG4-RD Responder Index (RI)], serological (ESR and CRP) and immunological (serum IgG4 and circulating plasmablasts) biomarkers. The enhanced liver fibrosis score was exploited as a biomarker for fibroblast activation. Results: Thirteen (65%) patients had two or more organs affected by IgG4-RD. All patients had active IgG4-RD as defined by a median IgG4-RD RI value of 9 (range 6–15; normal < 3). Serum IgG4 and plasmablasts were elevated in 85% of patients. Circulating plasmablasts positively correlated with PVC-SUV (P = 0.027), inversely correlated with TLGtot−ln (P = 0.023) and did not correlate with TLGtot+ln (P > 0.05). No statistically significant correlation was found between PVC-SUV or TLG and IgG4-RD RI, ESR, CRP, serum IgG4 or enhanced liver fibrosis score (P > 0.05). Clinical response to immunosuppressive therapies was associated with a consensual reduction of circulating plasmablasts, PVC-SUV, TLGtot+ln and TLGtot−ln values (P < 0.05 for all comparisons). Conclusions: 18 F-FDG uptake of IgG4-RD lesions reflects immunological perturbations of the B cell compartment rather than fibroblast activation and extracellular matrix deposition. Conventional biomarkers of disease activity, namely IgG4-RD RI, ESR, CRP and serum IgG4 levels, do not appear to correlate with the radiometabolic activity of IgG4-RD lesions. In light of our results PET/CT represents a reliable instrument for assessing IgG4-RD activity, although lymph-node uptake deserves careful interpretation.